Innovative Approaches to Addressing the Fundamental Materials Challenges in Advanced Water Splitting Technologies for Renewable Hydrogen Production. (6th January 2017) - Klahr, Benjamin M; Peterson, David; Randolph, Katie; Miller, Eric L.
Abstract : The emergence of hydrogen and fuel cell technologies offers important and potentially transformative environmental and energy security benefits. In recent years, research supported by the U.S. Department of Energy's Fuel Cell Technologies Office has contributed substantially to the development and advancement of these technologies. The research investments to reduce costs in fuel cell stacks, for example, are clearly paying off, as commercial fuel-cell electric vehicles are being rolled out by major car manufacturers today. With increasing market penetration of FCEVs, enabling technologies for the affordable and widespread production of clean, renewable hydrogen is becoming increasingly important. Long term commercial viability of renewable hydrogen in the commercial marketplace will rely on continued materials research on several important fronts. Examples include the discovery and development of efficient, durable, and cost effective materials, devices and systems for hydrogen production based on: (1) low and high temperature advanced electrolysis powered by renewable electricity sources; (2) direct low-temperature photoelectrochemical water splitting powered by sunlight; and (3) direct high-temperature solar thermochemical water splitting. Research innovations in macro-, meso- and nano-scale materials are all needed for pushing forward the state-of-the-art in these areas. Such innovations are being facilitated by the DOE Energy Materials Network (EMN) initiative which aims to accelerate materials research and development (R&D) for clean energy applications through the streamlined utilization of advanced scientific resources in theory, computation, experimentation, analysis, and data informatics. The "HydroGEN" EMN consortium on Advanced Water Splitting Materials for renewable hydrogen production will be described and discussed.